2020
DOI: 10.1029/2019gl086147
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Observation of Negatively and Positively Charged Nanograins at Comet 67P/Churyumov‐Gerasimenko

Abstract: Observations near comet 67P by Rosetta show evidence of charged nanograins. Specifically, the ion and electron sensor (IES) observed negative particles with energy/charge (E/q) consistent with charged nanograins. However, theory predicts that both polarities should be present. On 19 September 2014, IES detected positively and negatively charged particles with E/q up to the maximum detectable by IES (~17 keV/q) coming roughly from the Sun. The arrival directions of the negative and positive particles were diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The latter is particularly clear in the simultaneous detection of positive as well as negative nanograins by LLera et al. ( 2020 ), where the deviation from antisunward motion is opposite for oppositely charged grains (Fig. 17 ).…”
Section: Plasmamentioning
confidence: 72%
“…The latter is particularly clear in the simultaneous detection of positive as well as negative nanograins by LLera et al. ( 2020 ), where the deviation from antisunward motion is opposite for oppositely charged grains (Fig. 17 ).…”
Section: Plasmamentioning
confidence: 72%
“…The presence of positively and negatively charged nanometer-sized grains at 67P/C-G have been reported by LLera et al (2020) based on measurements of Ion Electron Sensor (IES), which was part of the Rosetta Plasma Consortium (Burch et al 2007). These IES observations of the grains showed that their arrival direction did not come from the nucleus but was instead more scattered.…”
Section: Discussionmentioning
confidence: 94%
“…Dual chevron MCP performance for singly charged species under numerous detection conditions have been extensively studied and generally find that as m/q increases, the detection efficiency decreases (Gilmore & Seah 2000;Fraser 2002;Liu, Li & Smith 2014). Large mass, highly charged species, on the other hand, have been found to have relatively constant detection efficiencies in event counting mode (Fontanese et al 2018;Gemer et al 2020;Llera et al 2020). For a specific example, highly charged iron dust particles in the size range of 100 to 2000 nm with 20 to 300 m s −1 velocities were detected with a 6 ± 1 % efficiency (Fontanese et al 2018).…”
Section: Methodsmentioning
confidence: 99%